HEARING THRESHOLD VALUE ON THE EMPLOYEE AIR SEPARATION PLAN PT.X - Hanis Prasetyaningtyas (Universitas Darussalam Gontor, 2018)
Noise at work can causse disruption to worker, one of which is a decrease in hearing threshold value. There are many things that cause decrease in hearing threshold value to worker like age, exposure time, length of work,obedience with personal protective equipment, and also history of illness. In this company, there is a part that cause noise that exceed thershold limit value, one of them is in the Air Separation Plan. This research was descriptive observational with cross sectional design. Population of this research was all worker on Air Separation Plan amounted to 12 people. The variable were age, exposure time, length of work, obedience with personal protective equipment, and also history of illness. The result of this research was intensity of noise in this plan is 126 dB. The age of worker start from 23- 47 y.o. The exposure time start from 5 – 15 minute. The most length of work was 1- 15 years. In obedience with personal protective equipment there were many worker are obedience with personal protective equipment. And most worker have no history of illness. The result was there are relation of obedience with personal protective equipment and history of illness with decrease in hearing threshold value in the worker of Air Separtion Plan. out of 12 worker there are 8 worker who did not have hearing loss and there were 4 worker that have hearing loss.Keyword :noise, thershold limit value, the obedience with personal protective equipment